Pemetaan Bidang Tanah Melalui Survei Lapangan Di Desa Dawan Kaler Kabupaten Klungkung Provinsi Bali - Ni Putu Lehni; Putra, I Wayan Krisna Eka; Budiarta, I Gede (Universitas Pendidikan Ganesha, 2024)
The one map policy will be implemented after all land parcels in Indonesia have been thoroughly mapped. In order to realise a complete Village/City map, regulations are needed that support the complete mapping of land parcels through the complete systematic land registration project. This mapping is done through field surveys to collect information on the ownership of land parcels in the village. The purpose of this research is to identify the distribution and factors of land parcels that have not been recorded on the working map of Dawan Kaler Village and to explain the process of mapping land parcels for registration on the working map. The method applied was descriptive qualitative. The results indicate that there are three categories of unregistered land parcels, namely unplotted, untidy, and overlapping. The main causes are the parcel owner and the measuring officer. The research also describes the method of improving the working map in the village.